Interspecies Recombination in Type II Topoisomerase Genes Is Not a Major Cause of Fluoroquinolone Resistance in Invasive Streptococcus pneumoniae Isolates in the United States - Pletz, Mathias W. R. (American Society for Microbiology, 2005)
Mutations in the topoisomerase type II enzymes account for fluoroquinolone resistance in Streptococcus pneumoniae. These mutations can arise spontaneously or be transferred by intraspecies or interspecies recombination, primarily with viridans streptococci. We analyzed the nucleotide sequences of the quinolone resistance-determining regions of 49 invasive levofloxacin-resistant pneumococcal isolates and did not find any evidence for interspecies recombination.